Positron emission tomography in hepatobiliary and pancreatic malignancies: a review - Lan, Billy Y.; Kwee, Sandi A.; Wong, Linda L. (The American journal of surgery, 2012)
The prognosis for hepatobiliary and pancreatic malignancies is dismal. Surgery remains the primary curative option, but unresectable disease is often discovered during operative exploration. Positron emission tomography (PET) provides unique biological information different from current imaging modalities. The role of PET in detecting hepatobiliary and pancreatic malignancies has not yet been established. The purpose of this article was to review the literature on the use of PET in hepatobiliary and pancreatic malignancies. We performed an extensive search on PubMed using PET and hepatocellular, pancreatic, gallbladder, and cholangiocarcinoma as keywords, excluding articles not written in English or on nonhuman subjects, case reports, and series with <5 patients. Although PET has shown usefulness in the diagnosis of certain cancers, current literature cautions against the use of PET for determining malignant potential of primary liver and pancreatic lesions. Literature on PET more strongly supports clinical roles for restaging of hepatobiliary and pancreatic malignancies, and for identifying metastatic disease.